Encapsulation of Heteropolyanion‐Based Ionic Liquid within the Metal–Organic Framework MIL‐100(Fe) for Biodiesel Production. Issue 3 (29th December 2014) - Wan, Hui; Chen, Chong; Wu, Zuowang; Que, Yigen; Feng, Yu; Wang, Wei; Wang, Lei; Guan, Guofeng; Liu, Xiaoqin
Abstract The front cover artwork for Issue 3/2015 has been provided by a research group from the State Key Laboratory of Materials‐Oriented Chemical Engineering, Nanjing Tech University. The image depicts a new strategy to construct a composite of an ionic liquid, a polyoxometalate, and a metal–organic framework. See the Full Paper itself at http://dx.doi.org/10.1002/cctc.201402800.